IMPLEMENTASI KURIKULUM MERDEKA DALAM MEMBANGUN KARAKTER SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NURUL QOMAR - Cecep Abdul Muhlis Suja'i (Program Studi Pendidikan Agama Islam, 2023)
This study aims to find out how the implementation of the merdeka curriculum in building student character in islamic religious education subjects, where this research method uses a qualitative approach, the location is at nurul qamar middle school, the data sources are informants, events, locations and documents, primary and secondary data, techniques data collection by participatory observation, interviews, and documentation. Analyzing the data interactively, while checking the validity of the data using credibility, transferability, dependability and confirmability. The results of the study show that in the implementation of the independent curriculum in building student character in pai mapel at nurul qomar middle school with several stages, namely planning, implementation, evaluation and there are inhibiting factors in the freedom learning-based islamic religious education learning in an effort to form student roots at nurul qomar middle school.